Postsecondary Teachers’ Perspectives on Effectively Engaging Learners in Today’s Post "Pandemic Pedagogy" Era - Deepak P Subramony (Educational Considerations, 2024)
This article presents the findings of a recent study surveying and interviewing post-secondary teachers within a college of education at a large, Carnegie "R1" public university in the Midwestern United States to unearth their perspectives of how to better engage their learners within the hybrid/multiple-modality instructional contexts that represent the new normal in today’s post "pandemic pedagogy" era. Within the current context of potentially emerging new variants of the SARS-CoV-2 virus and/or other pathogens, it also discusses key findings related to the teachers’ views regarding the current levels of institutional support they receive to this end, and their perspectives regarding how said support could be improved.
Keywords: engagement; online learning; hybrid learning; pandemic pedagogy; higher education